Pediatric acute liver failure: An experience of a pediatric intensive care unit from resource limited settings - Amatya, Puja; Kapalavai, Sudeep Kumar; Deep, Akash; Sankaranarayanan, Srinivas; Krupanandan, Ravikumar; Sadasivam, Kalaimaran; Ramachandran, Bala (Frontiers in Pediatrics, 2022)
Introduction Pediatric acute liver failure is a rare and serious disease. Though liver transplantation is considered as the established treatment option for patients who will not recover with medical management. Due to advancement of medical care there has been increase in spontaneous regeneration of liver, obviating the need for liver transplantation. We identified the etiologies, outcome and prognostic factors of acute liver failure and the validity of the existing liver transplantation criteria to predict the outcome of pediatric acute liver failure. Materials and Methods This was a retrospective study done from January 2014 to December 2019 in a tertiary pediatric critical care unit in South India. All children aged between 1 month to 18 years admitted with acute liver failure were enrolled. Results Of 125 children with acute liver failure, the main etiologies were infections (32%), indeterminate (23%), paracetamol toxicity (21%), metabolic (13%) and others (11%). Dengue was the most common infection (55%). The median paediatric logistic organ dysfunction score at admission was 12 (4-27). Of 125 patients, 63.2% (n=79) had spontaneous regeneration which was higher in paracetamol induced (92.3%) compared to non-paracetamol induced acute liver failure (55.5%). Only two patients underwent liver transplantation and 35% died. Peak alanine transaminase and use of inotropes significantly predicted the outcome of disease. Of 38 children meeting King’s College Hospital criteria for liver transplantation, 57.9% had spontaneous regeneration and 36.8% died. Of 74 children meeting INR >4 criteria, 54% (n=40) had spontaneous regeneration and 43.2% died. INR >4 criteria was more sensitive than King’s College Hospital criteria for predicting the need for liver transplantation. Conclusion Pediatric acute liver failure is caused by varied etiologies and infections were the commonest cause. Despite having a seriously ill cohort of patients, medical management resulted in spontaneous regeneration in the majority of children with acute liver failure. The use of inotropes, advanced hepatic encephalopathy, and peak alanine transaminase were predictors of poor outcome in children with acute liver failure and these patients could be considered for liver transplantation as available. Therefore, we may need to develop better predictors of pediatric acute liver failure in resource limited settings.